THE EFFECT OF PACKAGE SERVICE QUALITY ON CUSTOMERS SATISFACTION (Studies on Customers of Jemur Andayani Post Office, Surabaya City) - Widya Puspa Prameswari; Ertien Rining Nawangsari (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
This research is motivated by the increasing number of package delivery services other than the post office which results in intense competition. While the object chosen in this study is the customer of the Jemur Andayani Post Office, Surabaya, where there has been a decrease in the level of package delivery at the Jemur Andayani Post Office and an increasing number of competitors. The purpose of this research was to determine the influence of service on satisfaction at Jemur Andayani Post Office. After literature review and formulating hypotheses, data were collected through quantitative methods using a questionnaire to 100 customers of the Jemur Andayani Post Office. This research uses an analytical method is simple linear regression analysis. The results of the hypothesis test show that the t value is 25.249. T value (25.249)> t table (1.660), then Ho rejected and H1 accepted. So there is a significant influence between package service quality on satisfaction at the Jemur Andayani post office, Surabaya